The Role of Oil Market in Explaining the Volatility of Gold and Foreign Exchange (Dollars/Euro) Markets - Nasser Khiabani; Manouchehr Dehghani (فصلنامه پژوهش‌های اقتصادی ایران, 2014)
Undoubtedly, new developments in information and trading technologies have increased the integration of international financial markets in the world. This in turn has generated interest in examining the volatility transmission of financial market across markets. In this paper, we investigate the co-movements and volatility transmission among the three important oil, gold and US dollar/euro exchange rate markets. Using weekly data from 1995 to 2012, we estimate a VAR-ABEKK-Mean model and find the evidence of return and volatility spillovers among the three markets. More specifically, we find strong evidence of significant transmission volatility from the oil market to the two other markets.  We also show that the transmission of information is asymmetric among the three markets. In this regard, the bad news of an increase  in oil prices appears  to be more influential than news of a decline in its value for investors in gold and exchange rate markets.